Weather eye - Howarth, Lesley (Cambridge, Mass. : Candlewick Press, 1997)
In England in 1999, thirteen-year-old Telly organizes her fellow climate observation club members to calm the planet's turbulent weather.
Booklist starred.
Horn Book.
School Library Journal.
Young Adult
Keywords: Natural disasters -- Fiction; Science fiction; Weather -- Fiction; Natural disasters -- Fiction; Science fiction; Weather -- Fiction; England -- Fiction; England -- Fiction